The Student Religion/Pluralism/Media/ Survey A Comparison of German and Turkish Secular High School Students from Research to Practice - F. Gould, Benina; B. Gould, Jeffrey (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The purpose of our research was to find out if high school students want more discussion and/or education about religion in their schools and to assess their tolerance to other religions.Methods: Two groups of secular high school students, German Non-Turkish and Turkish were asked questions about religious identity, Pluralism, and social media. To assess religious tolerance, they were presented a picture of each religious symbol.Results: Our study identified that students wanted more information about religions and our findings suggest that to encourage Pluralism and Religious Tolerance it is important to develop curriculum that will introduce students to different religions and to develop training to facilitate teachers’ educational interventions.Implications: Before one can build effective public policy for religious/pluralistic education, it is important to know more about young people and their religious belief systems. Because religion plays a significant role in history and society, pluralistic religious education is essential to understanding both the nation and the world.